2018
DOI: 10.1371/journal.pone.0192559
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of the LPS core glycosyltransferase WapH for cold adaptation in the Antarctic bacterium Pseudomonas extremaustralis

Abstract: Psychrotroph microorganisms have developed cellular mechanisms to cope with cold stress. Cell envelopes are key components for bacterial survival. Outer membrane is a constituent of Gram negative bacterial envelopes, consisting of several components, such as lipopolysaccharides (LPS). In this work we investigated the relevance of envelope characteristics for cold adaptation in the Antarctic bacterium Pseudomonas extremaustralis by analyzing a mini Tn5 wapH mutant strain, encoding a core LPS glycosyltransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Finally, in common with that observed for other cell envelope components, transcriptome analyses have shown an upregulation of genes involved in biosynthesis of outer membrane components, with LPS biosynthetic genes (mainly glycosyltransferases) and outer membrane proteins being upregulated at low temperatures (De Maayer et al 2014;Frank et al 2011;Gao et al 2006). In agreement with this, a recent study showed how mutation of a core LPS glycosyltransferase gene (wapH) impaired growth of an Antarctic bacterium at low temperatures (Benforte et al 2018).…”
Section: Cell Wall: Outer Membranementioning
confidence: 57%
“…Finally, in common with that observed for other cell envelope components, transcriptome analyses have shown an upregulation of genes involved in biosynthesis of outer membrane components, with LPS biosynthetic genes (mainly glycosyltransferases) and outer membrane proteins being upregulated at low temperatures (De Maayer et al 2014;Frank et al 2011;Gao et al 2006). In agreement with this, a recent study showed how mutation of a core LPS glycosyltransferase gene (wapH) impaired growth of an Antarctic bacterium at low temperatures (Benforte et al 2018).…”
Section: Cell Wall: Outer Membranementioning
confidence: 57%
“…In the Antarctic bacterium Pseudomonas syringae Lz4w, it was observed that low temperatures caused changes in the composition and fluidity of LPS as higher polymyxin B sensitivity was detected along with an increased amount of hydroxy fatty acids [ 58 ]. In another Antarctic Pseudomonas — P. extremaustralis —the relevance of the core integrity of the LPS to cope with cold was evidenced by analyzing a wapH mutant strain, encoding a core LPS glycosyltransferase [ 59 ]. The wapH strain was impaired to grow in the cold.…”
Section: Envelopes and Cold Adaptationmentioning
confidence: 99%
“…Changes in these characteristics were also observed when P. extremaustralis was grown at different temperatures. These results indicate that LPS appears as a novel essential feature for active growth under cold conditions [ 59 ].…”
Section: Envelopes and Cold Adaptationmentioning
confidence: 99%
“…When S. putrefaciens was cultivated at 10, 4, and 0 • C, no significant differences (p > 0.05) in the content of total lipids and phospholipids were found among these three treatments. The importance of lipids composition in membranes for bacteria to survive under cold stress has been generally agreed [4,33,43]. Changes in lipids response to cold stress have been reported in different species of bacteria [2,44]; however, limited information is available on lipidomics, as stated in the Introduction.…”
Section: Lipidomic Data Processingmentioning
confidence: 99%